Nanoscale optical and structural characterisation of silk - Ryu, Meguya; Honda, Reo; Cernescu, Adrian; Vailionis, Arturas; Balčytis, Armandas; Vongsvivut, Jitraporn; Li, Jing-Liang; Linklater, Denver P.; Ivanova, Elena P.; Mizeikis, Vygantas; Tobin, Mark J.; Morikawa, Junko; et al. (Beilstein Journal of Nanotechnology, 2019)
The nanoscale composition of silk defining its unique properties via a hierarchial structural anisotropy needs to be analysed at the highest spatial resolution of tens of nanometers corresponding to the size of fibrils made of β-sheets, which are the crystalline building blocks of silk. Nanoscale optical and structural properties of silk have been measured from 100 nm thick longitudinal slices of silk fibers with ca. 10 nm resolution, the highest so far. Optical sub-wavelength resolution in hyperspectral mapping of absorbance and molecular orientation were carried out for comparison at IR wavelengths of 2–10 μm using synchrotron radiation. A reliable distinction of transmission changes by only 1–2% as the anisotropy of amide bands was obtained from nanometer-thin slices of silk.
Keywords: absorbance; anisotropy; retardance; silk